IMPLEMENTASI PENERAPAN SISTEM EKONOMI TERBUKA DI INDONESIA (Sebuah Tinjauan Terhadap Q.S. Mulk ayat 15) - M. Farhan Rosyidi; Nur Aidah Rahmah; Sufiyani; Alfira Dwi A; Dinda Rizky Meidiana; Ani Faujiah (ICO EDUSHA, 2021)
The purpose of this paper is to find out the implementation of an open economic system in Indonesia based on QS Al Mulk paragraph 15. This economic openness Indonesia occupies 68 levels in the world according to GIEO. Indonesia is taking full advantage of strategic trade relations in Southeast Asia so that foreign capital flows support the current account balance. Then the Governments are required to improve the management of resources so as not to hinder exports and imports as well as God who encourages people to seek sustenance and work. This research is a library research that uses library materials as the main material in this research. The results of this study show that Indonesia implements an open economic system that cannot be separated from the threat of recession, but Indonesia has managed to manage its resources well, so that Allah gives benefits to His creatures. Keywords: Impact, Implementation, Open Economy, International Trade, Status References Chalid, N. (2013, Desember). Peranan Ekspor Dalam Perekonomian Riau. Jurnal Ekonomi, 21, 14. Https://Www.Google.Com/Amp/S/Www.Cips-Indonesia.Org/Amp/Keterbukaan-Ekonomi-Bantu-Perkuat-Perekonomian-Nasional Https://Www.Studocu.Com/Id/Document/Universitas-Gadjah-Mada/Business/Dampak-Keterbukaan-Ekonomi-Di-Indonesia/1891315 Persentase Ekspor Indonesia Terbaru. (T.Thn.). Dipetik November 08, 2021, Dari Www.Bps.Go.Id: Https://Www.Bps.Go.Id/Pressrelease/2021/04/15/1821/Ekspor-Maret-2021-Mencapai-Us-18-35-Miliar-Dan-Impor-Maret-2021-Senilai-Us-16-79-Miliar.Html Rahmi Nuraini P.P., D. M. (2019). Analisis Pengaruh Keterbukaan Ekonomi Terhadap Pertumbuhan Ekonomi. Jurnal Dinamika Ekonomi Pembangunan, 2, 20-35. Safitriani, S. 2014. Buletin Ilmiah Litbang Perdagangan: Perdagangan Internasional Dan Foreign Direct Investment Di Indonesia, Vol 8 (1). Setiawan, H., Dan Lestari, S. 2011. Perdagangan Internasional. Yogyakarta: Pustaka Nusantara. Tafsir Surah Al-Mulk Ayat 15. (T.Thn.). Dipetik November 08, 2021, Dari Tafsirweb.Com: Https://Tafsirweb.Com/11043-Surat-Al-Mulk-Ayat-15.Html Veritia, Dkk. 2019. Teori Ekonomi Makro. Jakarta: Unpam Press. Chalid, N. (2013, Desember). Peranan Ekspor Dalam Perekonomian Riau. Jurnal Ekonomi, 21, 14. Https://Www.Google.Com/Amp/S/Www.Cips-Indonesia.Org/Amp/Keterbukaan-Ekonomi-Bantu-Perkuat-Perekonomian-Nasional Https://Www.Studocu.Com/Id/Document/Universitas-Gadjah-Mada/Business/Dampak-Keterbukaan-Ekonomi-Di-Indonesia/1891315 Persentase Ekspor Indonesia Terbaru. (T.Thn.). Dipetik November 08, 2021, Dari Www.Bps.Go.Id: Https://Www.Bps.Go.Id/Pressrelease/2021/04/15/1821/Ekspor-Maret-2021-Mencapai-Us-18-35-Miliar-Dan-Impor-Maret-2021-Senilai-Us-16-79-Miliar.Html Rahmi Nuraini P.P., D. M. (2019). Analisis Pengaruh Keterbukaan Ekonomi Terhadap Pertumbuhan Ekonomi. Jurnal Dinamika Ekonomi Pembangunan, 2, 20-35. Safitriani, S. 2014. Buletin Ilmiah Litbang Perdagangan: Perdagangan Internasional Dan Foreign Direct Investment Di Indonesia, Vol 8 (1). Setiawan, H., Dan Lestari, S. 2011. Perdagangan Internasional. Yogyakarta: Pustaka Nusantara. Tafsir Surah Al-Mulk Ayat 15. (T.Thn.). Dipetik November 08, 2021, Dari Tafsirweb.Com: Https://Tafsirweb.Com/11043-Surat-Al-Mulk-Ayat-15.Html Veritia, Dkk. 2019. Teori Ekonomi Makro. Jakarta: Unpam Press.